Penganggaran Pendapatan dan Penjualan pada PT Tunas Harapan Meubelindo, Kota Medan - Sumatera Utara - Andoko Andoko; Frinan Satria; Friyan Satria (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
Company can increase the profit from the sales and revenue. Every company should prepare the budgeting of the sales and revenue to maximize the profit. Budgeting is one way to estimate the number of sales that marketing people will reach the target. Budgeting reveals the strategic plan of a business unit, organization, activity or event in a measurable manner. Budgeting lies at the foundation of any financial plan. Budgeting lies at the foundation of any financial plan. PT Tunas Harapan Meubelindo is a company who is trading in ceramics. In increasing the profit, they need to have budgeting in sales in cooperation with the marketing department. With good budgeting in sales, company can have strategic planning.